Pengaruh Media Picture Story terhadap Kemampuan Berpikir Kritis Siswa pada Materi Biologi - Khoirul Umam (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Picture story is one of learning media that use picture as main tool in learning process. Because with the image can improve the reasoning power of students so that students' critical thinking skills over time will appear. This study aims to determine whether the media Picture Story effect on students' critical thinking skills on biological materials. In this study using two classes as research sample that is experiment class and control class. The design of this study type of data used is quantitative data in the form of data from post test results in the form of values or numbers. After the test, there were differences in post test results from both samples indicating that students' critical thinking skills were better than control classes. So it can be concluded that the Picture Story media affect the students' critical thinking skills on biological materials.